Aerodynamically-shaped cyclone shelters for Queensland. Issue 2 (3rd July 2019) - Holmes, John; Ginger, John; Mullins, Peter
ABSTRACT: This paper describes some features of public cyclone shelter design for tropical North Queensland Australia. These buildings are required to resist very high wind and windborne-debris speeds, in the context of apparently increasing numbers of very severe tropical cyclones affecting the Queensland coastline. An interesting aspect of the standard shelter design is the corner shaping and venting of the roof and walls, which are shown to significantly reduce the local wind pressures.